COMBUSTION TEMPERATURE ANALYSIS ON CO EMISSIONS IN A SIMPLE LIGHTWEIGHT BRICK-BASED INCINERATOR - Made Ardikosa Satrya Wibawa; I Made Anom Adiaksa; I Made Agus Putrawan; I Wayan Suma Wibawa; Anak Agung Gede Pradnyana Diputra; I Wayan Agus Rantia Dana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Residual waste management at the community level remains a significant environmental problem, particularly for mixed organic and inorganic waste. The use of a simple incinerator made from lightweight bricks is a practical solution due to its low construction costs and ease of operation. However, incomplete combustion can produce harmful gas emissions such as carbon monoxide (CO). This study aims to analyze the effect of combustion temperature on CO levels produced by a simple three-level incinerator using wood fuel. The incinerator design consists of an ash chamber on the lower level, a wood combustion chamber on the middle level, and a waste combustion chamber on the upper level with a volume capacity of 0.384 m³. The residual waste burned is 10 kg per cycle consisting of a mixture of organic and inorganic waste. Data collection was carried out 20 times by measuring the combustion temperature and CO levels using a gas analyzer. The results show an inverse relationship between combustion temperature and CO levels. Increasing the combustion temperature results in a more complete oxidation process, resulting in a significant decrease in CO levels. This study demonstrates that controlling combustion temperature is an important parameter in improving combustion efficiency and reducing harmful gas emissions in small-scale incinerators.